Case report: Spontaneous renal hemorrhage in anti-neutrophil cytoplasmic antibody-associated vasculitis - Ruohan Yu; Lina Zhang; Ting Long; Hui Gao; Jing Xu; Tong Zhang; Shengguang Li (Frontiers in Immunology)
Anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic necrotizing vasculitis that predominantly affects small vessels. In this report, we present a typical case of granulomatosis with polyangiitis (GPA) complicated by spontaneous renal hemorrhage (SRH), a rare but potentially severe condition. The patient developed SRH during immunosuppressive therapy but recovered following conservative treatment. We then conducted a systematic literature review on SRH in the context of AAV, and analyzed clinical features, management strategies, and patient prognosis. A total of 15 patients were enrolled for statistical analysis, comprising the one case reported in the current study and 14 from the literature. Of these patients, nine presented with GPA and six showed microscopic polyangiitis (MPA), with a sex distribution of 3:2 males to females. The average patient age was 54.5 years, and ranged from 25 to 82 years. Acute flank pain was the most common clinical manifestation, and was occasionally accompanied by anemia and shock. Treatment varied for the different patients. Eight patients received glucocorticoid and immunosuppressive agents that included rituximab, cyclophosphamide, and azathioprine; five patients underwent transcatheter arterial embolization (TAE); and one patient underwent nephrectomy. Our findings indicate that SRH typically occurs early in the course of AAV and correlates with disease activity, with renal aneurysm rupture as the primary cause. More than half of the patients respond well to corticosteroids and immunosuppressants. Timely TAE is essential for patients showing persistent deterioration despite conservative management.